Exploring the TPACK of Grade 9 mathematics teachers in the Western Cape of South Africa - Morris, Leigh (School of Education, 2022)
The Department of Basic Education is striving towards improving the Grade 9 mathematics TIMSS results (Department of Basic Education, 2019). The use of technology in the mathematic classroom has shown to be able to transform mathematical education (Wiest, 2001) and, if implemented correctly in South Africa, educational technology could improve learner performance in these key areas (Western Cape Education Department, 2012). However, it appears as if South African teachers are not able to effectively integrate technology into their classrooms and professional development in this area is necessary (Saal, Graham & van Ryneveld, 2020). This Masters thesis uses a rubric based around Niess's four domains of knowledge to examine three Grade 9 Mathematics teachers' TPACK through a deep dive case study into their teaching practices during the period of COVID-19 in South African classrooms. It seeks to understand how teachers are using technology in their lessons and what areas of TPACK need to be developed within Grade 9 mathematics teachers. Evidence from this study shows that Grade 9 mathematics teachers appear to be comfortable using technology themselves in their classrooms but need guidance in learner-centred technology use. The evidence also shows that smaller classroom sizes due to COVID-19 mean that teachers appear to be more confident with the use of technology in their half-size classrooms over the sizes pre COVID-19. The results demonstrate the need for professional development aimed at learner-centred technology use, and that, in order for this usage to occur, assessment of classroom sizes needs to occur to assist in developing confidence in teachers to allow for more learner-centred use of technology in the classroom.